Interfacial bond behaviour between hybrid carbon/basalt fibre composites and concrete under dynamic loading - Yuan, C.; Chen, Wensu; Pham, Thong; Hao, Hong; Cui, J.; Shi, Y. (ELSEVIER SCI LTD, 2020)
An experimental investigation on the dynamic interfacial bond behaviours between hybrid carbon/basalt fibre reinforced polymer (FRP) sheets and concrete under high loading velocities (i.e., 8.33E-6, 1.0, 3.0, and 8.0 m/s) is carried out in this study. The single-lap shear specimens are evaluated with different stacking sequences of FRP sheets (i.e., CFRP and BFRP) bonded to the concrete substrates. Experimental results including debonding failure modes, ultimate debonding strain, debonding load, interfacial fracture energy, and bond-slip response are discussed and evaluated. The testing results show that the interfacial bond behaviours between either sole FRP sheet or hybrid carbon/basalt FRP composite and concrete are sensitive to strain rate. The sole FRP sheet exhibits higher strain rate sensitivity than hybrid composite. The interfacial shear resistance between hybrid FRP sheets and concrete is improved due to the effect of FRP hybridization and strain rate. Additionally, the stacking sequence of FRP composites results in different bond performance when the loading speed is less than 1 m/s, while the effect of stacking sequence on bonding behaviour is insignificant when the loading speed is over 1 m/s. The hybrid composites have a relatively longer effective bond length under both quasi-static and dynamic loadings. Empirical formulae are proposed based on the test data to predict the dynamic interfacial bonding strength and shear stress between single or hybrid FRP sheet and concrete at various strain rates.